A 2d numerical model of salinity distribution pattern on the estuary of Jeneberang River - Riswal Karamma (Lowland Technology International, 2020)
Hydrodynamic factors and aquatic environment at the mouth ofthe Jeneberang River are a major concern for the managementof coastal areas and estuaries because can affect estuaryutilization activities. This study uses a two-dimensionalnumerical model to reveal the dynamic and physicalcharacteristics of the waters during the dry season at the mouthof the Jeneberang River. Measurements of tides, flow velocity,temperature and salinity were carried out prior to usingnumerical modeling to describe the tidal-driven flow circulation.The simulation model shows that the salinity distribution patternfollows the flow pattern so that it affects the distribution of thesalinity distribution. The modeling results show a decrease insalinity downstream of the Janebarang River estuary. Theupstream part has a relatively high salinity compared to thedownstream part, between 36.4 PSU - 36.8 PSU. Thedownstream part of the water has a salinity level ranging